Phylogeography of Oligosarcus acutirostris (Characiformes: Characidae): testing biogeographic hypotheses in the Northeastern Mata Atlântica freshwater ecoregion - Vida Souza; Leonardo Oliveira-Silva; Rayana Tiago Dutra; Priscila Camelier (Neotropical Ichthyology, 2023)
Abstract The Northeastern Mata Atlântica freshwater ecoregion (NMAF) is recognized for the high degree of endemism of its ichthyofauna, whose evolutionary and biogeographic histories are still poorly understood. Oligosarcus acutirostris is a freshwater fish species endemic to the NMAF, which is distributed in coastal rivers and streams draining Bahia, Espírito Santo, and part of Minas Gerais states in eastern Brazil. Its widespread distribution in currently isolated river basins along the NMAF prompted this study, which aimed to understand what scenarios would be involved in determining its current distribution pattern, and to contribute to a better understanding of the biogeographic history of the NMAF. For this, mitochondrial and nuclear DNA sequences were analyzed based on samples from different localities along the species distribution, including its type locality. Overall, phylogeographic analyses indicate a strong genetic structure within the species evidenced mainly by the non-sharing of haplotypes between most of the basins analyzed. According to the AMOVA results, the current distribution of haplotypes is better explained by the Pleistocene coastal paleodrainages. The results are also used to test and complement a biogeographic hypothesis previously proposed for the drainages of the NMAF.